Preconceito linguístico: um estudo do comportamento linguístico dos alunos da área rural da estrada de Beja - RODRIGUES, Maria Odaléia Barbosa (2023)
The present about the study linguistics of the students of the district farm of the road next Beja and the preconception linguistics that these students endure in the school. The schools, mostly the publics, are today haunter for students of some places that have manifestation and dialects different. The true of the language to be conditional and model for reality social and cultural do it an instrument that represent reflection meaningful on the process of learning these students. Have this in view, this work is may be pertinence because care of theme very important for the learning Brazilian actual: the preconception linguistics how being an aggravating on the indiscipline in the class of lesson. On the specifications case, the specify case, the community of the rural place that have your proprio dialect that is a of the coefficients of discrimination and inferior of the subjective, include your history and culture. Look for about of the inquiry bibliographic to consult authors with acknowledged contribution on the if reference the theme of the inquiry, such with Bagno (2002), Beveniste (1989), Luft (2001). The field inquiry happens on the Esmerina Bou-Habib high school. For data collection was applied two conferences with seven questions for two teachers of Portuguese language and other with group of students of the 6th year in same school.